Optimasi Pola Tanam Daerah Irigasi Rotiklot Kabupaten Belu - Berek, Margaretha Gloria; Bunganaen, Wilhelmus; Messah, Yunita A. (P3M- Politeknik Negeri Kupang, 2024)
This research was carried out with the help of an optimization program using Quantity Methods for Windows 3 software. The value of irrigation water requirements was calculated using a method based on Irrigation Planning Criteria - 01 of 2013. The data used in the analysis were irrigation area area data, rainfall data and 15 year climate data and planting pattern data. In this research, four initial planting alternatives were planned with the number of planting seasons in a year being three and the planting period being 10 days. The calculation results show that the maximum mainstay volume occurred in February at 19741.58 m3 and the mainstay volume in January, March, April, May, June, July, August, September, October, November and December was constant at 19354.84 m3. The maximum water requirement for rice plants occurs in the first initial planting alternative in planting season 3, amounting to 3.09 lt/sec/Ha and secondary crops occurs in the third initial planting alternative in planting season 3, amounting to 1.63 lt/sec/Ha. The results of optimizing the planting pattern in the Quantity Methods for Windows 3 software obtained results greater than the existing land area with a size of 300% of 27 Ha, which means that the planting pattern resulting from the optimization is Optimum